Pengaruh Viral Marketing Mixue Terhadap Keputusan Pembelian: Survei Pada Followers Instagram @mixueindonesia - Alvin Ramadhan; Oktaviana Purnamasari (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
Social media is social media, where users can easily participate freely, share, and create several things such as blogs, social networks, forums, and also virtual worlds and social networks are the most commonly used form of social media. by people around the world. The purpose of this research is to determine Viral Marketing, Purchase Decisions for Mixue products among @mixueindonesia Instagram Followers, and to determine the Influence of Viral Marketing on Purchase Decisions among @mixueindonesia Instagram Followers. The theory used is that Instagram content includes videos, advertisements, and content and Purchase Decisions include awareness, interest, evaluation, trial, and adoption. The approach in this research is quantitative with a survey method. The data collection technique was carried out by distributing questionnaires given to 73 respondents on @mixueindonesia Instagram followers. Sampling used the Slovin technique. The questionnaire collection method used was simple random sampling. The results of this research show that the influence of Viral Marketing as a whole, respondents responded well (agree), as well as the influence of Viral Marketing Mixue on Purchasing Decisions. Overall, respondents responded well (agree) to all the Y variable statements in the research questionnaire. The results of calculations from this research data showed that The t-count value is greater than 8.357, which is greater than the t-table value of 1.666. Because the t-count is greater than the t-table, H0 is rejected and H1 is accepted. And the magnitude of the influence of Viral Marketing @mixueindonesia has a moderate or moderate influence of 0.496 on purchasing decisions with a percentage of 49.6%, while the remaining 50.4% is influenced by other factors outside the research.